Two-valved seed vessels - Hubbard, Jonathan, author; Voss, Gary Wayne, committee member; Nelson, Chris, committee member (Colorado State University. Libraries, 2004)
My thoughts and artwork are inspired by my great admiration and attraction to nature and natural forms. In my artwork, I draw upon the strength of nature and its beautiful delicacies, to create forms that are strong and bold. All of my pieces of artwork that I create use a variety of traditional metalsmithing techniques. The media I have chosen to construct these pieces of art is mild steel. By using steel as the main media, I am able to transform its cold harsh surface into something that is inviting and natural. It is this manipulation of the material that I am also intrigued by. I see all of my artwork as vessels or pod structures. These structures are studies that document the ever-changing stages of the media selected. Some of my pieces reflect strength and a solid volume, while others contain soft and fragile elements that portray the stages of growth followed by cracking, decaying, and death.
Keywords: Metal sculpture